Respuesta agronómica del cultivo de pepino (Cucumis sativus) a la aplicación del bocashi elaborado con Jacinto de agua (Eichhornia crassipes) - Solis Pérez, Jennifer Maribel (2022)
The present research was focused on studying the adequate doses of fertilization for an optimum development of the cucumber crop. The general objective was to evaluate the agronomic response of the cucumber crop to the application of Bocashi made with water hyacinth. The research project was developed at the Experimental Campus "La Maria" belonging to the State Technical University of Quevedo, located on the Quevedo-El Empalme road, in the province of Los Rios.